Bidirectional authentication key agreement protocol supporting identity’s privacy preservation based on RLWE - Yatao YANG; Xinguang HAN; Jierun HUANG; Yang ZHAO (Tongxin xuebao)
In order to solve the problem of identity privacy preservation between two participants involved when implementing authenticated key agreement protocol,a bidirectional authenticated key agreement protocol against quantum attack based on C commitment scheme was proposed.Through the design of C commitment function,the real identity information of two participants involved was hidden.Based on RLWE difficult problem,under the premise to ensure identity anonymity,this protocol not only completed two-way identity authentication,but also ensured the integrity of the transmitted message,furthermore,the shared session key was negotiated.After been analyzed,in terms of protocol’s execution efficiency,only two rounds of message transmission were needed to complete anonymous two-way authentication and key agreement in the proposed scheme.Compared with Ding’s protocol,the length of public key was reduced by nearly 50%.With regard to security,the protocol could resist forgery,replay,key-copy,and man-in-the-middle attacks.It is proved that the proposed protocol satisfies the provable security under the eCK model.At the same time,the protocol is based on the RLWE problem of lattices,and can resist quantum computing attacks.